Metode Pemberitaan Injil Rasul Paulus Di Atena Berdasarkan Kisah Para Rasul 17:16-32 Dan Implementasinya Pada Masa Kini - Sari, Intan Betesda; Sumiwi, Asih Rachmani Endang (Sekolah Tinggi Teologi Berita Hidup, 2024)
Every believer must be a witness as confirmed in Acts 1:8 and of course must be accompanied by the leadership of the Holy Spirit. The Apostle Paul always preached the gospel at every opportunity he had, he realized that his life must be a witness to God. Athens was one of the cities visited by the Apostle Paul and Paul was sad when he saw that this city believed in idolatry. The strategy used by the Apostle Paul in preaching the Gospel in Athens can be seen in the book of Acts 17:16-34. This research uses a descriptive-analytic method, with an exegetical approach to the text of Acts 17:16-34, which focuses on